Impact of a nudge-based food environment intervention in a hospital convenience store on staff’s food intake and Na/K - Teruko Kawabata; Masakazu Nakamura; Yukari Takemi; Fumi Hayashi; Takashi Yamada (BMC Nutrition, 2024)
Abstract Background A food environment intervention using nudge tactics was implemented at a hospital convenience store (CVS) in Tokyo to improve employees’ eating habits. The objective of this study was to evaluate its effects on the urinary sodium-to-potassium ratio (Na/K), food intake, eating attitude, and behavior. Methods Using a pre–post design; the intervention incorporated nudge tactics, healthier options, easy-to-pick food placement, and eye-catching information. We also used price incentives. The primary outcomes included changes in Na/K and sodium and potassium excretion assessed using spot urine samples at health checkups. Secondary outcomes were changes in staff food intake, eating attitude, and behavior which were assessed using questionnaire surveys. All outcomes were evaluated statistically. Furthermore, we investigated how the intervention led to outcomes using path analysis. Results A total of 140 participant (52men and 88women) were analyzed. Significant changes were observed in Na/K (3.16 to 2.98 in median, p = 0.02) and potassium excretion (43.4 to 45.2 mmol/day in mean, p = 0.03). However, sodium excretion did not change significantly. The intake of fruits and dairy products increased with improved self-efficacy. The most influential factor for lowering Na/K and increasing potassium excretion was information from the CVS; purchasing “balanced meals” to lower Na/K and salads to increase potassium excretion were second. Conclusions Food environment intervention using nudge tactics can improve staff’s food intake and lower Na/K. Trial registration Registration number: UMIN000049444 (UMIN-CTR). Date of registration: November. 7. 2022.